Health literacy on HIV/AIDS and adherence to antiretroviral treatment: the moderating role of social support - Pujaannicha, Pujaannicha; Widiana, Herlina Siwi (International Journal of Public Health Science (IJPHS), 2025)
The increasing prevalence of HIV/AIDS continues to pose a significant global health challenge, with developing countries experiencing the fastest growth in transmission rates, including Indonesia. This quantitative correlational study examined the influence of HIV/AIDS-related health literacy on adherence to antiretroviral (ARV) therapy among people living with HIV/AIDS (PLWHA), with peer social support considered as a moderating variable. Participants included 208 PLWHA residing in Majalengka Regency, West Java, Indonesia. Data were gathered using standardized instruments measuring HIV/AIDS health literacy, treatment adherence, and peer social support, and were analyzed through moderation analysis using Jamovi software. The results demonstrated that HIV/AIDS health literacy had a significant positive effect on ARV adherence, and that peer social support strengthened this relationship. Nonetheless, the study is limited by its cross-sectional design and reliance on self-reported measures, which may restrict causal inference and generalizability.